Infusions of AP5 into the basolateral amygdala impair the formation, but not the expression, of step-down inhibitory avoidance - Roesler,R. (2000)
We evaluated the effects of infusions of the NMDA receptor antagonist D,L-2-amino-5-phosphonopentanoic acid (AP5) into the basolateral nucleus of the amygdala (BLA) on the formation and expression of memory for inhibitory avoidance. Adult male Wistar rats (215-300 g) were implanted under thionembutal anesthesia (30 mg/kg, ip) with 9.0-mm guide cannulae aimed 1.0 mm above the BLA. Bilateral infusions of AP5 (5.0 µg) were given 10 min prior to training, immediately after training, or 10 min prior to testing in a step-down inhibitory avoidance task (0.3 mA footshock, 24-h interval between training and the retention test session). Both pre- and post-training infusions of AP5 blocked retention test performance. When given prior to the test, AP5 did not affect retention. AP5 did not affect training performance, and a control experiment showed that the impairing effects were not due to alterations in footshock sensitivity. The results suggest that NMDA receptor activation in the BLA is involved in the formation, but not the expression, of memory for inhibitory avoidance in rats. However, the results do not necessarily imply that the role of NMDA receptors in the BLA is to mediate long-term storage of fear-motivated memory within the amygdala.